INFLUENCE OF PERCEIVED FAIRNESS AND TAX POLICY ON MOTOR VEHICLE TAX COMPLIANCE - Sembiring, Oloan; Riza, Fahrul (Universitas Riau, 2025)
Previous studies on tax compliance have primarily focused on individual and economic determinants, leaving limited understanding of how social and perceptual factors jointly influence taxpayers’ behavior. This study examines the effects of tax socialization and social environment as independent variables, with tax literacy serving as a mediating variable affecting tax compliance. It also introduces perceived fairness and tax policy as moderating variables, offering a broader analytical framework compared to prior research. Using data collected through proportional sampling in D.I. Yogyakarta and West Java, the study applies the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method to assess both direct and indirect relationships among variables. The results indicate that effective tax socialization and a supportive social environment significantly enhance tax literacy, which in turn promotes taxpayer compliance. Theoretically, this study contributes to the expansion of behavioral tax compliance models by integrating social and policy dimensions. Practically, it offers insights for policymakers to improve compliance through targeted education, social engagement, and the development of fair and consistent tax policies.